A theoretical assessment on sustainable wellbeing indicators for people interrelationships - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Zen, Ismawi; Abdullah, Alias (Malaysian Institute of Planners, 2017)
Sustainable well-being is the well-being attained without compromising others' opportunities to pursue their happiness. The concept of well-being is not merely personal, relational, organizational or communal issues, but rather the synergy of all four dimensions. The four dimensions of well-being are distinguishable, but they are inseparable entities. While focusing on subjective measure of well-being some research fail to interrogate the influence of contextual dynamics on respondents who report high levels of well-being despite living in deprived community conditions. This study argues that there could not be well-being without the combination of personal, relational, organizational and communal wellness.